Assistance in Designing Citarum River Cliff Protection to Control River Erosion in Atirompe Village, Majalaya District, Bandung Regency - Rohmat, Faizal Immaddudin Wira; Ledowikj, Felix Joel; Rodiah, Siti; Rohman, Mutiara Indah Nur; Burnama, Nabila Siti; Darsono, Sri Legowo Wignyo; Kuntoro, Arno Adi; Farid, Mohammad; Nugroho, Eka Oktariyanto; Chaidar, Ana Nugranah (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2023)
Rivers are often used as a water source for agriculture, transportation, and water supply needs. One of the causes of riverbank damage is scouring the cliff's foot, which cannot withstand scouring currents. If not addressed immediately, it will cause more severe damage. Citarum River is one river that passes through Atirompe Village, Majalaya District. The riverbanks in the area have a risk of cliff failure. The study objective was to analyze the problem, design the protection, and calculate the budget. The hydrology and riverbank analysis of the Majalaya River has been performed. The steps were essential to analyze the depth and width of the scour caused by the flow of the Citarum River water. Sediment data were collected at three locations, namely the upstream, middle, and downstream of the river segment that will be reviewed. In data processing, to obtain a sediment rating curve, it is necessary to measure the flow velocity, which will later be calculated and used as the flow rate during Total Suspended Solid (TSS) data collection. Using the Hydrology Engineering Center – River Analysis System (HEC – RAS) 6.2 software, the calculations with the Ripley Equation were compared to obtain the scour depth. For the design alternative, constructing a steel sheet pile-type cliff protection structure is one form of planning to protect riverbanks. This study also analyzed the recapitulation of the budgeting for protecting the Citarum riverbanks in Atirompe Village, Majalaya District. Using a standardized unit price, the total cost for the protection is 1.8 billion rupiahs.